Eucommia ulmoides leaves and Gardenia extracts promote white adipocyte browning by inhibiting autophagy - XIONG Shaofeng, HU Zhi, FANG Yang, ZHAO Le, ZHANG Jie, GUO Muying, WEI Li, WANG Kun (Xin yixue, 2025)
Objective To investigate whether extracts of Eucommia ulmoides leaves and Gardenia have the effects on promoting white adipose browning， and to explore their possible mechanisms. Methods The effects of Eucommia ulmoides leaves and Gardenia extracts on mature 3T3-L1 cells were detected using CCK8 assay， Western blotting， qRT-PCR， Oil red O staining， BODIPY staining， and mitochondrial fluorescent dye. Subsequently， autophagy inhibitors （rapamycin） were used to explore their possible mechanisms of action. Results Eucommia ulmoides leaves and Gardenia extracts could upregulate browning-related proteins and mRNAs （PRDM16， PGC-1α and UCP-1） （all P < 0.05）， inhibited autophagy-related proteins （Beclin-1 and p62） and mRNAs （LC3， Beclin-1 and p62） and the expression of autophagosomes （all P < 0.05）， inhibited lipid droplet accumulation， and increased mitochondrial abundance. The use of autophagy activator （rapamycin） restored the autophagy effect of Eucommia ulmoides leaf and Gardenia extracts on 3T3-L1 cells （all P < 0.05）， and it was found that the browning effect of Eucommia ulmoides leaf and Gardenia extracts on 3T3-L1 cells was also reversed by autophagy activator （all P < 0.05）. Conclusion Extracts of Eucommia ulmoides leaves and Gardenia have the effects upon promoting the browning of white adipocytes by inhibiting autophagy， demonstrating potential clinical applications in the clinical prevention and treatment of obesity and related metabolic diseases.